Fear of failure and Identification of business opportunities: differences between gender in the context of Covid-19 (National Administration Journal, 2022)
When starting a business, identifying opportunities is key for its proper development. However, fearing failure could be a vital asset, even more in crisis such as Covid-19. This research shows, based on a solid database of Colombia’s entrepreneurship (the survey of adult population of GEM, 2020), that there is a gap between men and women regarding fearing failure, but not in regard to identifying opportunities. There have been consistent findings on literature and related academic contributions, showing that these statistics has not changed through Covid-19.
Keywords: entrepreneurship; covid-19; economic crisis; emerging countries; fear of failure; business opportunity